Early experience with the ATTUNE Total Knee Replacement System - Giaretta, Stefano; Berti, Mattia; Micheloni, Gian Mario; Ceccato, Alberto; Marangoni, Francesco; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2019)
Background: Modern TKA implants promise to improve functional outcomes, stability, patient satisfaction and operating room efficiency. The purpose of this retrospective study is to evaluate our short-term clinical and radiological results and survival using the ATTUNE Total Knee Replacement System. Methods: The authors reviewed 228 primary cemented TKAs using ATTUNE Total Knee Replacement System which were implanted between 2014 and 2018 concerning short-term clinical and radiographical outcomes and survival. Clinical evaluation was performed using the Knee injury Osteoarthritis Outcome Score (KOOS), the Oxford Score and a Numeric Rating Scale (NRS) for pain. Radiographic analysis was performed using the Modern Knee Society Score Evaluation System. Results: The means of the clinical results as measured with KOOS score were Pain 82,7, Symptoms 79, ADL 78,3, Sport and recreation 51,8 and QOL 78,6. The mean Oxford score was 35 and NRS 2. The mean ROM was 113,4 (SD 9,4 range 90-130). Radiographically mean mechanical axis was 1,97° of Varus and radiolucent lines were detected in 43 knees (22,4%). The survival rate is 98.4% at 2 years and 97.4% at 5 years. Conclusion: At short-term follow-up the ATTUNE Knee Replacement System provide excellent clinical and radiographical outcomes and good results regarding revision rate. Due to high incidence of radiolucent lines, those patients should be closely monitored even though they show no clinical evidence for loosening.